2017
DOI: 10.3892/mmr.2017.6845
|View full text |Cite
|
Sign up to set email alerts
|

Syringic acid inhibits apoptosis pathways via downregulation of p38MAPK and JNK signaling pathways in H9c2 cardiomyocytes following hypoxia/reoxygenation injury

Abstract: Syringic acid (SA), a naturally occur-ring O‑methy-lated trihydroxybenzoic acid monomer extracted from Dendrobium nobile Lindl., has been demonstrated to attenuate renal ischemia‑reperfusion (I/R) injury. However, the role of SA in myocardial I/R injury is unclear. The present study aimed to clarify the cardioprotective effect of SA in myocardial I/R injury in vitro and explore the potential molecular mechanisms. In the present study, it was revealed that pretreatment with SA increased the viability and inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…24 In the current study, the activation of JNK and p38MAPK signaling was also observed to be enhanced by hypoxia, as the phosphorylation levels of JNK and p38MAPK were significantly upregulated by hypoxia as compared to normoxia (both P < .001, Figure 2A,B). And the enhanced activation of these two signalings participates in the progression of myocardial ischemia.…”
Section: Hypoxia Promoted the Activation Of Jnk And P38mapk Signalingsupporting
confidence: 64%
“…24 In the current study, the activation of JNK and p38MAPK signaling was also observed to be enhanced by hypoxia, as the phosphorylation levels of JNK and p38MAPK were significantly upregulated by hypoxia as compared to normoxia (both P < .001, Figure 2A,B). And the enhanced activation of these two signalings participates in the progression of myocardial ischemia.…”
Section: Hypoxia Promoted the Activation Of Jnk And P38mapk Signalingsupporting
confidence: 64%
“…Betulinic acid protects H9c2 cells from MI/RI by inhibiting oxidative stress and apoptosis, and the Nrf2/HO-1, JNK, and p38 pathways are involved in mediating these protective effects [ 264 ]. Syringic acid, a natural O-methylated trihydroxybenzoic acid monomer that is extracted from Dendrobium nobile Lindl., protects H9c2 cardiomyocytes from H/R-induced apoptotic injury via inhibiting the activation of the p38 MAPK and JNK signaling pathways [ 265 ]. Injection of snakegourd peel, a traditional Chinese herbal medicine, inhibits the apoptosis of myocardial cells by reducing intracellular Ca 2+ overload, inhibiting the activation of caspase-3, and downregulating the phosphorylated JNK (p-JNK) and p38 MAPK (p-p38 MAPK) protein expression [ 266 ].…”
Section: Interventions Targeting Oxidative Stress and Related Pathways In Myocardial Reperfusionmentioning
confidence: 99%
“…Syringic acid (4-Hydroxy-3,5-dimethoxybenzoic acid) is a naturally occurring phenolic compound mainly found in fruits of edible plants and mushrooms (Itoh et al, 2009;Pacheco-Palencia, Mertens-Talcott, & Talcott, 2008). It has wide range of pharmaceutical applications including antioxidant (Gao et al, 2018;Wang et al, 2016;Zhou et al, 2017), anti-diabetic (Muthukumaran, Srinivasan, Venkatesan, Ramachandran, & Muruganantham, 2013), hepatoprotective (Itoh et al, 2009;Itoh et al, 2010;Yan, Wang, Yen, Lee, & Yin, 2016), antihyperlipidemic (Ramachandran, 2010), cardioprotective (Ding et al, 2017;Rasheeda, Bharathy, & NishadFathima, 2018), neuroprotective (Rasheeda et al, 2018;Tokmak et al, 2017), and anti-inflammatory properties (Ham et al, 2016;Lee et al, 2012). Syringic acid extracted from Herba dendrobii has potential inhibiting activity on aldose reductase and its gene expression and thereby suppresses the diabetic cataract in eye lenses of rat model (Wei et al, 2012).…”
Section: Introductionmentioning
confidence: 99%